Pranksters vs. Autocrats : Why Dilemma Actions Advance Nonviolent Activism - Popovic, Srdja; McClennen, Sophia A. (Book collections on Project MUSE., 2020)
""This book explores the concept of "dilemma action," which offers a structured, strategic approach to effective nonviolent struggle. Dilemma actions are designed to create a response dilemma or lose-lose situation for public authorities by forcing them to either concede some public space to protesters or make themselves look absurd or heavy-handed by acting against the protest." --Provided by publisher"--